Low Advanced Lung Cancer Inflammation Index Predicts Poor Prognosis in Locally Advanced Nasopharyngeal Carcinoma Patients Treated with Definitive Concurrent Chemoradiotherapy. (7th October 2020) - Topkan, Erkan; Ozdemir, Yurday; Kucuk, Ahmet; Guler, Ozan Cem; Sezer, Ahmet; Besen, Ali Ayberk; Mertsoylu, Huseyin; Senyurek, Sukran; Kilic Durankus, Nulifer; Bolukbasi, Yasemin; Selek, Ugur; Pehlivan, Berrin
Abstract : Purpose . We aimed to retrospectively investigate the prognostic worth of pretreatment advanced lung cancer inflammation index (ALI) in locally advanced nasopharyngeal carcinoma (LA-NPC) patients treated with concurrent chemoradiotherapy (C-CRT). Patients and Methods . A total of 164 LA-NPC patients treated with cisplatinum-based definitive C-CRT were included in this retrospective cohort analysis. The convenience of ideal pre-C-CRT ALI cut-offs affecting survival results was searched by employing the receiver operating characteristic (ROC) curve analyses. The primary endpoint was the link between the ALI groups and overall survival (OS), while cancer-specific survival (CSS), locoregional progression-free survival [LR(PFS)], distant metastasis-free survival (DMFS), and PFS comprised the secondary endpoints. Results . The ROC curve analyses distinguished a rounded ALI cut-off score of 24.2 that arranged the patients into two cohorts [ALI ≥ 24.2 ( N = 94) versus < 24.2 ( N = 70)] with significantly distinct CSS, OS, DMFS, and PFS outcomes, except for the LRPFS. At a median follow-up time of 79.2 months (range: 6–141), the comparative analyses showed that ALI < 24.2 cohort had significantly shorter median CSS, OS, DMFS, and PFS time than the ALI ≥ 24.2 cohort (P < 0.001 for each), which retained significance at 5- (P < 0.001 ) and 10-year (P < 0.001 ) time points. In multivariate analyses, ALI < 24.2 was asserted to be an independent predictor of the worse prognosis for each endpoint (P < 0.001 for each) in addition to the tumor stage (T-stage) (P < 0.05 for all endpoints) and nodal stage (N-stage) (P < 0.05 for all endpoints). Conclusion . As a novel prognostic index, the pretreatment ALI < 24.2 appeared to be strongly associated with significantly diminished survival outcomes in LA-NPC patients treated with C-CRT independent of the universally recognized T- and N-stages.